2015
DOI: 10.1120/jacmp.v16i2.4917
|View full text |Cite
|
Sign up to set email alerts
|

Technical evaluation of different respiratory monitoring systems used for 4D CT acquisition under free breathing

Abstract: Respiratory monitoring systems are required to supply CT scanners with information on the patient's breathing during the acquisition of a respiration‐correlated computer tomography (RCCT), also referred to as 4D CT. The information a respiratory monitoring system has to provide to the CT scanner depends on the specific scanner. The purpose of this study is to compare two different respiratory monitoring systems (Anzai Respiratory Gating System; C‐RAD Sentinel) with respect to their applicability in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 10 publications
1
32
0
Order By: Relevance
“…De Groote17 proposed a model showing that if there exists asynchrony between motions along the dorsoventral and lateral directions with respiration, there will be a phase shift between the anterior–posterior movement (as measured as the RPM signal) and the change in abdominal perimeter (as measured as the ANZAI belt signal). In addition, in previous studies comparing different external surrogates,13, 16, 18 shape distortion can be observed between the respiratory traces in patients, which has not been investigated in those studies.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…De Groote17 proposed a model showing that if there exists asynchrony between motions along the dorsoventral and lateral directions with respiration, there will be a phase shift between the anterior–posterior movement (as measured as the RPM signal) and the change in abdominal perimeter (as measured as the ANZAI belt signal). In addition, in previous studies comparing different external surrogates,13, 16, 18 shape distortion can be observed between the respiratory traces in patients, which has not been investigated in those studies.…”
Section: Introductionmentioning
confidence: 93%
“…Several respiratory monitoring systems using external surrogates are available in the market for the purposes of measuring respiratory motion for 4D CT imaging and gated treatment 5. These systems measure the respiratory motion as the surface movement of abdomen or chest wall (eg, Real‐Time Position Management [RPM],4 C‐RAD,13 GateCT14), or the pressure change in a belt wrapped around the abdomen (eg, ANZAI,15 Bellows16), etc. There is no consensus of which is the best external surrogate with respect to the correlation with the internal tumor motion.…”
Section: Introductionmentioning
confidence: 99%
“…However, both techniques use ionizing radiation which should be reduced to a minimum according to the ALARA-principles [2]. Moreover these techniques lack the ability to sufficiently monitor intrafractional movements of the target caused by respiratory, cardiac or gastrointestinal motion [3]. …”
Section: Introductionmentioning
confidence: 99%
“…A median of 93% duty cycle was observed for 5 mm threshold band and a median of 52% for 2 mm. Since no smoothing filters were applied when collecting the Anzai data (raw data) and the system, like many, is known to have an inherent noise component [20,21], we believe that the duty cycle for the 2 mm and 5 mm threshold band could be slightly higher than reported here. Example of the noise peaks are denoted in (Fig.…”
Section: Discussionmentioning
confidence: 81%